Evaluation of the foreign exchange markets in Guyana - Ganga, Gobind Nauth (Institute of Development Studies. University of Guyana TurkeyenGY, 1994)
Discusses the theoretical determinants of the foreign exchange rate from the perspective of the monetary and portfolio approaches. Focuses on the nature of the foreign exchange markets in Guyana. Assesses the determinants of short-run foreign exchange movements in Guyana and provides some policy recommendations.